2021
DOI: 10.1186/s12915-021-01106-0
|View full text |Cite
|
Sign up to set email alerts
|

Stop codon readthrough alters the activity of a POU/Oct transcription factor during Drosophila development

Abstract: Background A number of cellular processes have evolved in metazoans that increase the proteome repertoire in relation to the genome, such as alternative splicing and translation recoding. Another such process, translational stop codon readthrough (SCR), generates C-terminally extended protein isoforms in many eukaryotes, including yeast, plants, insects, and humans. While comparative genome analyses have predicted the existence of programmed SCR in many species including humans, experimental pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…A recent study demonstrated that the vvl gene produces long and short isoforms through a stop codon readthrough process in the PG during larval development ( Zhao et al, 2021 ). Stop codon readthrough is a phenomenon in which near-cognate tRNAs are able to decode stop codons as sense codons, resulting in a read-frame extension even in a conventional 3′ untranslated region.…”
Section: Transcription Factors To Regulate the Expression Of Hallowee...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated that the vvl gene produces long and short isoforms through a stop codon readthrough process in the PG during larval development ( Zhao et al, 2021 ). Stop codon readthrough is a phenomenon in which near-cognate tRNAs are able to decode stop codons as sense codons, resulting in a read-frame extension even in a conventional 3′ untranslated region.…”
Section: Transcription Factors To Regulate the Expression Of Hallowee...mentioning
confidence: 99%
“…Stop codon readthrough is a phenomenon in which near-cognate tRNAs are able to decode stop codons as sense codons, resulting in a read-frame extension even in a conventional 3′ untranslated region. While the error rate of translational termination should be less than 0.1%, surprisingly, the stop codon readthrough of vvl mRNA reaches a rate of 50% in the PG ( Zhao et al, 2021 ). Consequently, the C-terminal extension of Vvl produces a long isoform, which possesses an extra 286 amino acid residues compared with the short isoform (427 amino acid length) encoded by the conventional vvl coding sequence.…”
Section: Transcription Factors To Regulate the Expression Of Hallowee...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the highly conserved NKX2.5 ( tinman in fly) which plays a crucial role in heart development is also a hotspot for genetic variants that have been linked to CHD ( McElhinney et al, 2004 ; Pashmforoush et al, 2004 ). In addition, the fly has an unprecedented arsenal of genetic tools that enable precise genetic manipulation to target specific developmental time points, or specific tissues and even cell-types within those tissues ( Hales et al, 2015 ; Zhao et al, 2021 ). Over the years many techniques to assay heart structure and function in the fly have been developed; these have consistently shown the physiological similarities of Drosophila and human heart development and function, as well as dysfunction when studying disease-associated genes and variants ( Wolf and Rockman, 2008 ; Manivannan et al, 2020 ).…”
Section: Drosophila Models Of Congenital Heart Disease (Chd)mentioning
confidence: 99%
“…Recently, tissue-specific TR was identified in a transcription factor Ventral veins lacking/Drifter ( Vvl/Dfr ). TR in Vvl/Dfr is necessary for regulation of several downstream genes and is crucial for larval development ( 31 ). For the majority of the candidates, the efficiency and the biological relevance of TR are not known.…”
Section: Introductionmentioning
confidence: 99%